2009
DOI: 10.4049/jimmunol.182.1.522
|View full text |Cite
|
Sign up to set email alerts
|

Activated Vγ9Vδ2 T Cells Trigger Granulocyte Functions via MCP-2 Release

Abstract: Vγ9Vδ2 T cells display a broad antimicrobial activity by directly killing infected cells and by inducing an effective adaptive immune response. The activation of Vγ9Vδ2 T cells by aminobisphosphonate drugs such as zoledronic acid (ZOL) results in a massive release of cytokines and chemokines that may induce a bystander activation of other immune cells. The aim of this work was to evaluate the ability of soluble factors released by ZOL-activated Vγ9Vδ2 T cells to induce granulocyte activation. We showed that so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 42 publications
1
34
1
Order By: Relevance
“…The observation that neutrophil counts were not affected by CD8 ϩ lymphocyte depletion suggests that the observed decrease in defensin expression reflects a system-wide transcriptional repression. Recent work has demonstrated that ␥␦ T cells are able to modulate the production of ␣-defensins in granulocytes (60) and ␤-defensins in epithelial cells (61). A few studies have reported that CD3 Ϫ CD8 ϩ cells (NK and ␥␦ T cells) produce defensins, and while we failed to detect significant levels of defensin mRNA, it remains formally possible that a portion of the observed decrease in defensin expression is in part related to their depletion (62)(63)(64).…”
Section: Microarray Analysis Of In Vivo Cd8contrasting
confidence: 51%
“…The observation that neutrophil counts were not affected by CD8 ϩ lymphocyte depletion suggests that the observed decrease in defensin expression reflects a system-wide transcriptional repression. Recent work has demonstrated that ␥␦ T cells are able to modulate the production of ␣-defensins in granulocytes (60) and ␤-defensins in epithelial cells (61). A few studies have reported that CD3 Ϫ CD8 ϩ cells (NK and ␥␦ T cells) produce defensins, and while we failed to detect significant levels of defensin mRNA, it remains formally possible that a portion of the observed decrease in defensin expression is in part related to their depletion (62)(63)(64).…”
Section: Microarray Analysis Of In Vivo Cd8contrasting
confidence: 51%
“…Among mucosal immune cells, γδ T-cells are known to be able to perform an antiviral activity by exerting a cytolytic activity, by releasing antiviral soluble factors [29,30] and by orchestrating the deployment of specific immune response [31,32]. Moreover, γδ T-cells are known to be specifically impaired during HIV infection [13,14,17,19].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in a prior study assessing the chemotaxis of human neutrophils, CCL8 synergistically enhanced neutrophil chemotaxis in the setting of low doses of IL-8 (85). Using a model of human ␥␦ T cell-monocyte coculture to study the effect of ␥␦ T cell activation on granulocyte function, another group showed that CCL8 promotes neutrophil degranulation (86). Future studies will assess the ability of CCL8 to promote neutrophil recruitment, degranulation, and phagocytosis.…”
Section: Fig 11mentioning
confidence: 96%